Canine Gliomatosis Cerebri: Morphologic and Immunohistochemical Characterization Is Supportive of Glial Histogenesis. Issue 2 (March 2021) - Rissi, Daniel R.; Donovan, Taryn A.; Porter, Brian F.; Frank, Chad; Miller, Andrew D.
Gliomatosis cerebri (GC) is a glioma subtype with diffuse neuroparenchymal infiltration without architectural distortion. GC was first used in human neuropathology and remained controversial until its elimination from the diagnostic lexicon in 2016. GC is currently defined as a diffuse growth pattern of glioma rather than a distinct entity. In this article, we characterize 24 cases of canine GC and classify these neoplasms as diffuse gliomas. Selected cases of canine GC were reviewed and immunolabeled for oligodendrocyte lineage transcription factor 2 (Olig2), glial fibrillary acidic protein (GFAP), and 2′, 3′-cyclic-nucleotide 3′-phosphodiesterase (CNPase). The mean age of affected dogs was 7 years, and 9 were brachycephalic. Gross lesions (8 cases) consisted mainly of parenchymal swelling. Histologically, of the 24 cases, there was widespread infiltration of neoplastic cells with astrocytic (12 cases), oligodendroglial (8 cases), or mixed morphology (4 cases) in the brain (18 cases), spinal cord (4 cases), or both (2 cases). Secondary structures occurred across different tumor grades and were not restricted to high-grade neoplasms. Astrocytic neoplasms had moderate nuclear immunolabeling for Olig2 and robust cytoplasmic immunolabeling for GFAP. Oligodendroglial neoplasms had robust nuclear immunolabeling for Olig2, moderate or absent cytoplasmic immunolabeling for GFAP, and moderate cytoplasmic immunolabeling for CNPase. Tumors with mixed morphology had robust nuclear immunolabeling for Olig2 and variable cytoplasmic immunolabeling for GFAP and CNPase. Morphologic and immunohistochemical features confirmed a glial histogenesis for all tumors and allowed for their classification as diffuse, low- or high-grade astrocytoma; oligodendroglioma; or undefined glioma. Further research is needed to confirm or refute the hypothesis that canine GC represents an infiltrative growth pattern of canine glioma.